EFFECTS OF METHANOL EXTRACT AND N-HEXANE EXTRACT OF PAPAYA LEAVES (CARICA PAPAYA L) ON TOTAL AND DIFFERENTIAL WHITE BLOOD CELL COUNTS IN MALE WISTAR RATS AFTER CARRAGEENAN INDUCTION - Okto P.E Marpaung; Datten Bangun; Syafruddin Ilyas (Universitas Muhammadiyah Sumatera Utara, 2019)
As one of the countries producing medicinal plants, Indonesia has the potential to develop medicinal plants in the future. The anti-inflammatory effects of methanol and n-hexane extract from papaya leaves were seen in this study using a pretest-posttest control group design using 36 male adult Wistar rats divided into 6 groups. All rats received 1 week acclimatization, then blood specimens were taken from the tail, after which they were treated, and intraplantar injections were carried out with 1% carrageenan solution as much as 0.1 ml. Then retrieval of blood specimens from rats' tails at 3 hours and 6 hours afterwards. Then an examination of the number and type of leukocytes was performed on all blood specimens obtained. It was found that the number of male Wistar rat leukocytes after getting methanol extract of papaya leaves was lower but not significant (p> 0.05) compared to those who did not. The increase in the number of leukocytes cannot be restrained significantly by the administration of n-hexane extract. It was found that changes in leukocyte counts in acute inflammatory conditions with the administration of methanol extract and n-hexane extract of Papaya Leaves. The increase number of neutrophils and monocytes in acute inflammatory conditions can be significantly suppressed by the administration of methanol extract of papaya leaves. Key words: inflammation, carrageenan, papaya, Carica papaya l